Electronic properties of (111) surface in crystals of A2B6 type - Zubkova, S.M.; Rusina, L.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
Electronic band structure, local densities of states (total and layer-resolved ones), and the distribution of a charge density of valence electrons (3D-graphics and contour cards) at the (111) polar surface in ZnTe, ZnS, CdTe crystals have been studied. The properties of anion- and cation-terminated surfaces have been analyzed separately. The self-consistent three-dimensional pseudopotential method has been used for numerical calculations in the framework of a model of layered superlattice. The application of an original iterator in the self-consistent procedure allowed the difficulties associated with the surface-induced presence of reciprocal-lattice vectors shorter than 1 a. u. to be overcome.